Ratgeberliteratur und Strategien der Normierung – am Beispiel von Wissenschaftsratgebern - Niemann, Robert (Studia Germanica Posnaniensia, 2019)
This article is going to follow up the question of normativization within counsellor texts, exemplarily using science guides. A pro argumentation for this is, to not only see normativization in this correlation as a morpho-syntactically and lexical medium – as we usually would – but beyond that also include patterned text structures. These are to be interpreted as appellative (and persuasive) strategies of the authors instance which ought to establish a relationship to the readers who are supposed to be guided by this foundation.